The trajectory of conditional, recurrence-free, and long-term survival in a complete 10-year cohort of patients with advanced ovarian cancer - Nina Groes Kofoed; Henrik Falconer; Matteo Bottai; Sahar Salehi (Acta Oncologica)
Background: The prognosis in advanced ovarian cancer is generally poor since the majority experience recurrence. Nevertheless, there is a chance of cure and very long-term survival may be achieved. However, traditional survival metrics do not account for the dynamic changes in prognosis over time. Our objectives were to examine conditional, very long-term and recurrence-free survival, in addition risk-factors for recurrence.